Transforming Health in Developing Nations: Paving the Way for an Integrated Health System - Pillay P; Ijoma GN; Ntwasa M; Moodley J (Journal of Healthcare Leadership, 2025)
Preenan Pillay,1,2 Grace Nkechinyere Ijoma,1 Monde Ntwasa,1 Jack Moodley3 1College of Agricultural and Environmental Sciences, University of South Africa, Roodepoort, Gauteng, South Africa; 2Insight, Waterfall City, Gauteng, South Africa; 3Women’s Health and HIV Research Group, Nelson R Mandela School of Medicine, School of Laboratory Medicine and Medical Sciences, University of Kwazulu-Natal, Durban, South AfricaCorrespondence: Preenan Pillay, Email ppillay01@gmail.comAbstract: The World Health Organization (WHO) recognizes the importance of Integrated Health Systems (IHS) in translating health information and its determinants into tangible outcomes. However, effective implementation of an IHS has not been realized due to the lack of a structured Health Information System (HIS) for centralized data analytics and accessibility. This is further exacerbated in developing nations because of the complex interplay between limited resources, inadequate infrastructure, and high disease burden. Therefore, the perspectives presented provide an enhanced engine in the form of a structured HIS to propel the IHS, such that the health system is driven by efficient health data management and analytics. The transformational IHS presented considers resource limitations within the context of the factors influencing political, structural, and economic reforms. This provides an adaptive and progressive approach to address multifaceted health challenges in developing nations. Importantly, the IHS framework presented provides a health system paradigm shift that integrates health practices and their determinants within an artificially intelligent-enabled data-driven architecture to achieve structured and seamless universal health coverage.Keywords: integrated health system, health information system, digitalization, health artificial intelligence, Enterprise Systems